Effects of Bee Venom Acupuncture on Surgically Induced Endometriosis in Rats - Yong-Hyun Lee; Eun-Mee Lim; Ki-Rok Kwon (Korean Pharmacopuncture Institute, 2006)
Purpose : Bee Venom Acupuncture(BVA) is known to affect inflammation and immune system. This study examined the macroscopic, hormonal and immunological effects of BVA on rats with surgically induced endometriosis. Method : Endometrial tissue was implanted in the serosal wall of the small intestine in rats. The rats were divided randomly into an experimental and control group. The experimental group was treated with BVA injection on kwanwon(CV4) three times per week, and the control group was given an oral dose of normal saline every day. 6 weeks later, the size of the ectopic uterine tissue was estimated, and the serum progesterone, estradiol and cytokine(TNF-α, IL-2, IL-4, IL-6, IL-10) concentrations were analyzed. Result : The size of the ectopic uterine implants in the experimental group was much smaller than that in the control group. The estradiol, IL-2 concentrations were significantly lower and the IL-6, IL-10 concentrations were significantly higher in the serum of the experimental group than in the control group. there was no significant difference in the concentration of the other cytokine. Conclusion : These results suggest that BVA is an effective treatment for endometriosis.